2019
DOI: 10.1590/0102-311x00246018
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Brazilian version of the HSOPSC: a reassessment study

Abstract: This study aimed to reassess the psychometric properties of the Hospital Survey on Patient Safety Culture (HSOPSC) adapted to Portuguese for use in the Brazilian context. An observational, cross-sectional study was performed in a large, private, non-profit, acute care hospital, reference in patient safety, in a major Brazilian metropolis. Participants were selected from a non-probability sample of all eligible personnel in the various hospital departments invited to participate in the study. Reliability of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
0
13
0
2
Order By: Relevance
“…32 Previous research also showed strong relationships between these 2 dimensions. 4,20,30,37 Communication openness and feedback and communication about error showed the second strongest relationship because both dimensions deal with communication, 32 and these dimensions were found to be correlated in previous research. 4,28,30 Similar to other research, 4,30,37 all HSOPSC factors were positively correlated with patient safety grade, the single-item outcome measure, which supports the convergent validity of the scale.…”
Section: Discussionmentioning
confidence: 67%
“…32 Previous research also showed strong relationships between these 2 dimensions. 4,20,30,37 Communication openness and feedback and communication about error showed the second strongest relationship because both dimensions deal with communication, 32 and these dimensions were found to be correlated in previous research. 4,28,30 Similar to other research, 4,30,37 all HSOPSC factors were positively correlated with patient safety grade, the single-item outcome measure, which supports the convergent validity of the scale.…”
Section: Discussionmentioning
confidence: 67%
“…Public and private hospitals in Brazil display different degrees of development and maturity as regards care quality and patient safety. Accordingly, similarly to previous studies of transcultural adaptation of the HSOPSC version 1.0 to the Brazilian context [ 11 , 29 , 30 ], all the items contained in the original version of the instrument were retained in the final version produced in the study reported here, as in the Indonesian study [ 21 ]. This study thus differed from the Korean study [ 10 ], which excluded the item A5R “This unit relies too much on temporary, float, or PRN staff”.…”
Section: Discussionmentioning
confidence: 99%
“…The 56% response rate obtained in this study was higher than those of Brazilian studies of transcultural adaptation of the HSOPSC version 1.0. A study at two large hospitals in southeast Brazil obtained a response rate of 38.5% [ 11 ]; another, at a large hospital in a major metropolis in Brazil had a response rate of 18.7% [ 30 ]. It is essential to achieve a high response rate to assure robust psychometric analyses and, in parallel, to understand the capillarity of safety culture in the context where the instrument is applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the knowledge of health team professionals about the definitions of adverse events and PS in care, the questionnaire "Hospital Survey on Patient Safety Culture" (HSOPSC) was applied, in the version adapted from the instrument that was translated and validated for the Brazilian context [17,20].…”
Section: Study Variablesmentioning
confidence: 99%